SLEEP QUALITY AND STRESS AMONG PRE-CLINICAL MEDICAL STUDENTS: A CROSS-SECTIONAL STUDY - Warih Andan Puspitosari; Pebriansyah Alldin; Nusaibah Mar'atush Shalihah (Faculty of Medicine Universitas Brawijaya, 2026)
Sleep quality and stress are critical issues among medical students at the end of the pre-clinical phase, who face high academic and psychological demands that place them at greater risk of sleep disturbances and increased stress. This study aimed to analyse the relationship between sleep quality and stress levels in medical students. A cross-sectional study was conducted among active sixth-semester medical students at Universitas Muhammadiyah Yogyakarta who agreed to participate; students who did not complete the questionnaire were excluded from the analysis. Purposive sampling was applied. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while stress levels were assessed using the Depression Anxiety Stress Scales-42 (DASS-42). Data were analysed using univariate and bivariate methods, and the association between sleep quality and stress levels was assessed using Spearman’s rho. A total of 141 students participated, most of whom were female (62.4%). The majority of participants had poor sleep quality (74.5%), and 24.8% experienced stress ranging from mild to very severe. Spearman’s rho test showed a statistically significant positive correlation between sleep quality and stress levels (r = 0.184; p < 0.05), indicating a weak correlation. These findings suggest that poor sleep quality is common among pre-clinical medical students and is associated with higher stress levels.